Oral ingestion of Shiikuwasha extract suppresses diabetes progression in db/db mice by preserving β-cell mass - Kaji, Megumi; Kaneko, Yukiko K.; Ihim, Stella Amarachi; Kanoh, Ran; Yamamoto, Moe; Yamaguchi, Momoka; Ishikawa, Tomohisa (Frontiers in Nutrition, 2024)
Introduction Nobiletin is a polymethoxyflavonoid abundant in citrus peels and has been reported to have various bioactive effects. We have previously reported that nobiletin inhibits endoplasmic reticulum stress-induced apoptosis in the pancreatic β-cell line INS-1 and that continuous subcutaneous administration of nobiletin suppresses the progression of diabetes by protecting β-cells in type 2 diabetic db/db mice. In the present study, we investigated effects of oral ingestion of Shiikuwasha extract rich in nobiletin on the pathogenesis of type 2 diabetes in db/db mice. Materials and methods A Shiikuwasha extract was dissolved in MediDrop sucralose. Twenty-four mice were equally divided in three groups and fed with vehicle or low or high dose of Shiikuwasha extract for 4 weeks. Blood glucose levels, pancreatic β-cell mass, serum insulin levels, pancreatic insulin content, and other biomarkers were measured and compared between the groups. Results The group that freely ingested the Shiikuwasha extract containing higher concentration of nobiletin (Shiikuwasha H) showed lower blood glucose levels. At the end of the experiment, the Shiikuwasha H group exhibited improved glucose tolerance, lower serum glycoalbumin levels, and an increase in β-cell area per pancreas compared with the control group. Body weight, food intake, and serum biomarkers related to liver function and lipid metabolism of the Shiikuwasha H group were not different from those of the control group, although water intake of the former was significantly decreased than that of the latter. Conclusion Our results suggest that the oral ingestion of Shiikuwasha extract preserves pancreatic β-cell mass in diabetic mice, which might be attributed to ameliorating the progression of diabetes.